Forms of temporality and historical time in the work of Johann Gottfried Herder
1 online resource.
Keywords: "This edited collection is the first volume solely dedicated to research on Johann Gottfried Herder's understanding of history, time, and temporalities. Forms of Temporality and Historical Time in the Work of Johann Gottfried Herder is ideal for scholars, graduates, and postgraduates interested in Herder's metaphysics, epistemology, and philosophy of history, as well as any scholar concerned with 18th-century concepts of time and the emergence of the modern world at the beginning of the 19th century"--